2011
DOI: 10.4314/sajrs.v33i1.65482
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two different forms of three-point line on game actions in girls’ mini-basketball

Abstract: Z=-3.269, p=.001), in hook shots (U=1358526, Z=-3.176, p=.001), in three-point shot attempts (U=1314902, Z=-6.600, p=.000), and in successful three-point shots (U=1355201, Z=-3.888, p=.000). This study confirms the necessity of consulting with analysts before introducing and modifying a rule in sport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 22 publications
(27 reference statements)
4
23
2
1
Order By: Relevance
“…Children should frequently achieve high values in accuracy and success to satisfy their preferences, have more fun and feel good (ASEP, 1996;ARIAS et al, 2009;ISAACS;KARPMAN, 1981;PALAO et al, 2004;PIÑAR, 2005;PIÑAR et al, 2007;REGIMBAL et al, 1992). In the present study, both variables increased with the 440-g ball.…”
Section: Discussionsupporting
confidence: 55%
“…Children should frequently achieve high values in accuracy and success to satisfy their preferences, have more fun and feel good (ASEP, 1996;ARIAS et al, 2009;ISAACS;KARPMAN, 1981;PALAO et al, 2004;PIÑAR, 2005;PIÑAR et al, 2007;REGIMBAL et al, 1992). In the present study, both variables increased with the 440-g ball.…”
Section: Discussionsupporting
confidence: 55%
“…Arias et al compared the effects of two shapes of the three-point line, among other variables, on the types of shots thrown. The results showed an increase in standard (35% vs. 40.5%) and hook shots (0.2% vs. 1%) when the three-point line was outlined by the free-throw lane [3].…”
Section: Introductionmentioning
confidence: 90%
“…After analyzing 431 basketball shots taken by children under 12 years of age, Ibáñez et al [14] found that 27.5% of attempted shots were lay-ups and 58.7% were standard shots. Arias et al [3] showed that 21.3% of attempted shots were lay-ups. In the present study with the 440-g ball, the percentage of attempted lay-ups was higher while the percentage of attempted standard shots was similar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations